Factors influencing discharge readiness among patients with mild-to-moderate ischemic stroke: a cross-sectional study - Wang Li-Fei; Samartkit Niphawan; Masingboon Khemaradee (Sciendo, 2024)
To describe discharge readiness and determine whether self-efficacy, social support, and the quality of discharge teaching can predict discharge readiness among patients with mild-to-moderate ischemic stroke.